Clinical Profile of Anti-Myelin Oligodendrocyte Glycoprotein Antibody Seropositive Cases of Optic Neuritis. (3rd September 2015) - Matsuda, Ryusaku; Kezuka, Takeshi; Umazume, Akihiko; Okunuki, Yoko; Goto, Hiroshi; Tanaka, Keiko
Abstract: We have studied the clinical picture of anti-aquaporin antibody (AQP4-Ab)– and anti-myelin oligodendrocyte glycoprotein antibody (MOG-Ab)–positive optic neuritis. However, optic neuritis associated with MOG-Abs has not been elucidated using new methods such as cell-based assay. Hence, we conducted a comprehensive investigation on its clinical profile. Serum samples from 70 patients (17 males and 53 females, mean age 43.1 years) with optic neuritis were tested for MOG-Abs by cell-based assay. In MOG-Ab seropositive patients, the disease type, recurrence status, and visual function outcome were analysed. Among 70 patients, 18 were MOG-Ab seropositive. The 18 patients comprised 2 with chronic relapsing inflammatory optic neuropathy, 2 with AQP4-Ab seropositive optic neuritis (neuromyelitis optica), 12 with idiopathic optic neuritis, and 2 with optic neuritis associated with multiple sclerosis. Excluding two cases that were also AQP4-Ab seropositive, MOG-Ab seropositive cases had relatively favourable visual acuity outcome (although not significantly different from seronegative cases) but had significant residual visual field deficit ( p  = 0.0015). Furthermore, the number of relapses of optic neuritis per year was significantly greater in MOG-Ab seropositive cases than in seronegative cases (0.82 vs. 0.40; p  = 0.0005). MOG-Abs may contribute to the heterogeneous clinical picture of optic neuritis, and although visual acuity outcome is favourable, there is a tendency of residual visual field deficit and a possibility of repeated relapses.